(untitled) (International Journal of Engineering and Computer Science, 2017)
Law is a general rule. Every human being presumed to intend his acts and this presumption of law prevails from consideration of all the evidence. This laws of crimes against women are considered as a set of rules (IF – THEN type) producing a knowledge base. Expert System or Knowledge Based System takes knowledge from this knowledge base, in the form of rules, fact, heuristics, semantic net and procedures. The expertise knowledge is stored in the knowledge base. The inference engine processes this knowledge, and makes decisions only if the rule is matched with input data. In this article, the author‟s gives study of research aspects of Expert System, its application in legal knowledge. Expert System used as reasoning strategies in different areas of legal domain.